Effect of GLP‐1 and GIP on C‐peptide secretion after glucagon or mixed meal tests: Significance in assessing B‐cell function in diabetes. Issue 6 (9th May 2017) - Guglielmi, C.; Del Toro, R.; Lauria, A.; Maurizi, A.R.; Fallucca, S.; Cappelli, A.; Angeletti, S.; Lachin, J.M.; Pozzilli, P.
Abstract: Background: The aim of the study was to investigate the different B‐cell responses after a glucagon stimulation test (GST) versus mixed meal tolerance test (MMTT). Methods: We conducted GST and MMTT in 10 healthy people (aged 25‐40 years) and measured C‐peptide, gastric inhibitory peptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) at different time points after the administration of 1 mg i.v. glucagon for GST or a liquid mixed meal for MMTT. Results: The GST stimulated C‐peptide showed a mean increase of 147.1%, whereas the mean increase of MMTT stimulated C‐peptide was 99.82% (Δincrease = 47.2%). Maximum C‐peptide level reached with the MMTT was greater than that obtained with the GST (C‐pept max MMTT = 2.35 nmol/L vs C‐pep max GST = 1.9 nmol/L). A positive and linear correlation was found between the GST incremental area under the curve C‐peptide and the MMTT incremental area under the curve C‐peptide (r = 0.618, P  = .05). After GST, there was no increment of GIP and glucagon like peptide‐1 levels compared to baseline levels. A positive and linear correlation between GIP and C‐peptide levels was observed only for the MMTT (r = 0.922, P  = .008) indicating that in the GST, the C‐peptide response is independent of the incretin axis response. Conclusions: Although the 2 stimulation tests may elicit a similar response in C‐peptide secretion, B‐cell response to MMTT depends on a functionally normal incretin axis. These results may have implications when investigating the B‐cell response in people with diabetes and for studies in which stimulated C‐peptide secretion is used as primary or secondary outcome for response to therapy.